A Critical Study of The Emperor Jones and The Yama Chao from the Perspective of Expressionism - Yu, Minghuang (Journal of Social Science and Humanities, 2025)
Expressionism is an important genre of modernism that comes arise at the beginning of 20th Century in Europe. It is a philosophical movement due to the modern industrialization, urbanization, social transformation and the World War which brought the shock to traditional culture and humanity from late 19th century to early 20th century in Western society. Expressionism generally includes the activities and creations of art, literature, drama, philosophy, architecture that fit the new culture, economic, society, politic of modern industrialize world. In China, after the New Cultural Movement in 1915, the trend of expressionism dramas in Western drama plays was adopted by Chinese drama writers and brought a short period of wave. This article mainly focuses on a comparative study of The Emperor Jones and The Yama Chao from the perspective of expressionism to show the core differences between two dramas.